Eco-friendly composite with matrix of recycled low-density polyethylene reinforced with wheat waste - Borges, Ianca Oliveira (2025)
The study investigated the effects of replacing varying amounts of straw and wheat husk residues on the properties of composites with a recycled low density polyethylene (LDPE) matrix. The composites were produced through the extrusion process, employing the following proportions: 0%, 10%, 20%, and 30% of wheat waste as reinforcement in the polymeric matrix. The agricultural wastes were reduced in particles and characterized in natura. The composites were shaped from pressing processes and their physical, mechanical and microstructural properties were evaluated. The results have shown an increase in water absorption for each 1% of wheat waste inserted in the composite of the order of 0.018%. The density of the composites decreased with the replacement of wheat waste by 4.8 g/cm3 for each 1% of replacement. The substitution of wheat waste increased the burning speed (flammability) when compared to recycled polymers (LDPE100%), indicating shorter fire spread time. There was a decrease in strength, modulus of elastic and tenacity, obtaining a material with high deformation.